Intrapreneurial Innovation in E-Commerce: Driving Fashion Business Growth - Nuryati, Marita Sri; Purbasari, Ratih; Purnomo, Margo (ITQAN: Journal of Islamic Economics, Management, and Finance, 2024)
This study explores the application of intrapreneurship principles in the growth of the e-commerce fashion brand CultureBasic. Through qualitative methods, the research involved in-depth interviews with the company owner to investigate the impact of intrapreneurship on product innovation, customer orientation, and marketing strategies. The results show that intrapreneurship significantly enhances company performance through key mechanisms: skill development via continuous training and education initiatives, effective collaboration that emphasizes strategic discussions and team synergy, and proactive leadership that is inclusive and adaptive. These findings affirm that intrapreneurial practices not only help maintain competitive advantage but also relevance in the dynamic digital era. The implementation of intrapreneurial principles at CultureBasic has proven capable of sustainably boosting product innovation and developing dynamic marketing strategies, which in turn increases customer satisfaction and loyalty, providing significant competitive advantages. The potential impact of these results indicates that applying intrapreneurial principles can drive sustainable and innovative business success across various industries.